Human Resource Management Based On Islamic Values At Madrasah Aliyah Nurul Qarnain In Facing The Challenges Of The Digital Era - Siti Maimunah; Qoidul Khoir (PT. Banjarese Pacific Indonesia, 2024)
In order to meet the difficulties of the digital age, this study intends to examine how Islamic educational institutions apply Human Resource management based on Islamic principles.. This study uses a qualitative method with a case study approach on an educational institution that applies Islamic principles in human resource management, such as trust, justice, and excellence. The research results show that the integration of Islamic values in human resource management significantly improves the performance, loyalty, and satisfaction of educators. However, the challenges in digital literacy are still felt by most educators, even though institutions have provided regular technology training. The implementation of a collaborative culture through deliberation has proven effective in enhancing innovation and the involvement of educators in the decision-making process. The use of digital technology tailored to Islamic values, such as sharia-compliant human resource management applications, also strengthens aspects of transparency and justice in institutional management. In conclusion, Human Resource management based on Islamic values, supported by digital technology, is capable of improving performance quality and creating a harmonious work environment that is relevant in addressing the challenges of the digital era.